Förändrade arbetsmarknadsförhållanden för högre utbildade? En studie av forskarutbildade i Finland 1990 - 2004 - Susanna Stén (The Research Institute of the Finnish Economy (ETLA), 2009)
The 1990's was a turbulent period for Finnish postgraduate education. The education system was reformed and the number of postgraduate students who graduated every year increased at a fast pace. In this thesis doctorate and licentiate degree holders as a group, as well as how their labour market situation has changed in the period of 1990-2004, is studied. The aim of the thesis is to describe the changes in the period rather than to try to explain them, since this is very complicated. The thesis uses the Finnish Longitudinal Employer- Employee Data (FLEED) that is maintained by Statistics Finland. The data cover a randomly chosen third of the Finnish population aged 16-69 in the years 1990-2004. The descriptive analysis shows that the composition of the group changed. Women's share of the postgraduate degree holders increased, as did the mean age among recently graduated, mostly because the share aged over 50 increased. The labour market situation of the postgraduate degree holders weakened during the period but was still good, all in all. There were remarkable differences between the different fields of study. Those with education in social and health care and in engineering enjoyed the most favourable conditions, while those with education in humanistic fields faced the least favourable labour market situation. The number of private sector employers with employees with postgraduate degrees doubled during the period. There were some differences between the firms employing postgraduate degree holders and the average firm in Finland. Moreover, the return to postgraduate education was estimated using regression analysis. Throughout the period, it seems that the return to postgraduate education remained unchanged. The marginal return to postgraduate education somewhat decreased during 1990- 1996, but thereafter the direction of the development is less clear. In 2004 a person with a postgraduate degree earned 101 percent more than a person with upper secondary education only and 16 percent more than a holder of a Master's degree. There were also obvious differences in earnings between postgraduate degree holders in different fields of study. Persons with a degree in social and health care earned 52 percent more than those with a humanistic degree in 2004. In the same year female postgraduate degree holders earned about 20 percent less than their male colleagues, but the wage differential across gender decreased during the period.
Keywords: J24; J44; 330; PhD; higher education; Finland; employment; wages; returns to education; Wissenschaftler; Studium; Arbeitsmarkt; Bildungsertrag; Finnland